Photonic crystal fibre as a potential medium for radiotherapy dosimetry. (August 2021) - Begum, Mahfuza; Rahman, A.K.M. Mizanur; Abdul-Rashid, H.A.; Yusoff, Z.; Mat Nawi, Siti Nurasiah; Khandaker, Mayeen Uddin; Bradley, D.A.
Abstract: Present study concerns the key thermoluminescence (TL) properties of photonic crystal fibres (PCFs), seeking development of alternatively structured TL materials that are able to offer a advantages over existing passive dosimeters. In terms of their internal structure and light guiding properties the PCFs, collapsed and structured, differ significantly from that of conventional optical fibres. To investigate the dosimetric parameters of the PCFs use was made of a linear accelerator producing a 6 MV photon beam, delivering doses ranging from 0.5 Gy to 8 Gy. The parameters studied included TL response, linearity index, glow curves, relative sensitivity and TL signal fading, the results being compared against those obtained using TLD-100 chips. At 4 Gy photon dose the Ge-doped collapsed PCFs were found to provide a response 27 × that of structured PCF, also giving a TL yield similar to that of standard TLD-100 chips. Over post-irradiation periods of 15 and 30 days collapsed PCF TL signal fading were 8% and 17% respectively, with corresponding values of 37% and 64% for the structured PCF. Trapping parameters including the order of kinetics (b), activation energy (E) and frequency factor (s -1 ) were assessed with Chen's peak shape method. Lifetime of trapping centre was found to be (2.36 E+03) s and (9.03 E +01) s regarding the collapsed and structured PCF respectively with 6 Gy of photon beam. For the Ge-doped collapsed PCF, the high TL yield, sensitivity and low fading provide the basis of a highly promising system of TLD for radiotherapy applications. Graphical abstract: Image 1 Highlights: Life time of trapping centre was found to be 2.36E+03 and 9.03E +01 regarding the collapsed and structured PCF respectively. Collapsed PCF gives rise by far to the greatest TL response, at some 27 × that of the structured PCF. The relative sensitivity of the Ge-doped collapsed and structured PCF with respect to standard TLD-100 were 0.94 and 0.03 respectively. During thirty days post irradiation, the Ge-doped collapsed PCF provides minimal fading 17% compared to the 64% loss of the structured PCF. The respective mean daily losses were 0.6% and 2%.